A imaginação de Kant e os dois objetos para nós: e ainda, a propósito da doutrina do esquematismo e das duas deduções das categorias - Olavo Calabria Pimenta (2012)
The thesis consists of four parts. In the first part a problem which was discovered during our research for the Philosophy Masters course (2003) is brought back. We had determined that Kant systematically uses two terms when referring to objects: Erscheinung (which was translated as appearance) and Phaenomenon (which was translated to phenomenon). Despite having initially perceived that the fundamental difference between these objects is related to conceptual representations that only the phenomena have, it was not possible to reach any satisfactory explanation for the purposes and consequences of such differentiation at that particular moment; which is why in the second part we dealt with another problem that is closely linked to the first: Kants Schematism. As Kant pledges that it is precisely in the context of schematism that the transformation of appearances in the phenomena takes place, it was believed possible to find the solution for the initial problem by identifying the taskthat the chapter of the Schematism of the Pure Concepts of Understanding performs on Critique of Pure Reason, as well as the characterization of the function of the three schemes. Considering the scarce exposure about the Schematism throughout Kants work, we decided to turn to the significant part of the debate about the theme elaborated by its interpreters. After an extensive bibliographic survey and the analysis of the most relevant interpretations, it was observed that the great disputing variety of interpretations, together with a surprising amount of different aspects, had only made us more aware of the complexity of the problems we were involved with. Even though we analyzed the conflictive positions by comparing them with Kants exposures we were not able to solve any of the two problems we had raised. Thus we decided to elaborate the third part of the work, proceeding towards a third problem. We realized it would still be necessary to come up with a satisfying characterization of Kants concept on the faculty of imagination, as it holds the responsibility of operating schematism, and by doing so, transforming the objects for us. Once again aided by background texts, especially some texts from Kant like the Anthropology from a Pragmatic Point of View (1798), we identified its five characteristic properties named status, character, aptitudes, impulses and conducts; and with this we were able to develop an original interpretation of the Kantian conception of the imagination. This consistent and promising results gave us conditions to solve at the fourth part of the thesis,and retrospectively, not only the two previous problems, but also found an unexpected outlet for a fourth and well-known question, namely, what would have been the reasons of the broad reformulation made by Kant on the chapter of Deduction of the categories for the second edition of Critique of pure Reason(1787). In light of the discoveries we made, the work is concluded by evaluating that these results were only achieved due to the joint treatment of these inextricably interwoven problems.